Understanding Hematological Toxicities Using Mathematical Modeling. Issue 4 (1st May 2018) - Fornari, Chiara; O'Connor, Lenka Oplustil; Yates, James W.T.; Cheung, S.Y. Amy; Jodrell, Duncan I.; Mettetal, Jerome T.; Collins, Teresa A.
Abstract : Balancing antitumor efficacy with toxicity is a significant challenge, and drug‐induced myelosuppression is a common dose‐limiting toxicity of cancer treatments. Mathematical modeling has proven to be a powerful ally in this field, scaling results from animal models to humans, and designing optimized treatment regimens. Here we outline existing mathematical approaches for studying bone marrow toxicity, identify gaps in current understanding, and make future recommendations to advance this vital field of safety research further.